Liturgia, ideología y ficción: hacia un estudio de las imágenes taumatúrgicas de Santiago Apóstol en el Siglo XII - Domínguez García, Javier (Revista de Filología Románica, 2008)
This article shows a new perspective on the interpretation of the Santiago’s representations as a miracle- worker in several texts of the Middle Ages.